Is Ambient Assisted Living the Panacea for Ageing Population? - d'Angelantonio, Marco (IOS Press, 2014)
The ageing population of Europe is a well-documented phenomenon and there is general agreement that it has serious implications for all European citizens as well as for policymakers and politicians. The current paradigm of caring for elderly citizens in residential homes is becoming untenable and it is also unpopular with many elderly people themselves. New ways of caring which engage and empower older adults more actively, and are also more cost-effective, must be found.